(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes methods for assessing the impact and effectiveness of translation strategies. The translation process is complex and multifaceted, and it plays an important role in language and intercultural communication. The article examines different types of translation strategies, including literal, adaptive, and contextual approaches. The advantages and disadvantages of each strategy are analyzed, as well as their impact on the target audience. The article also presents criteria used to assess translation effectiveness, such as accuracy, originality, and cultural adaptation. The authors demonstrate how different strategies are used in real life through practical examples. As a result, the article provides important recommendations for identifying and developing effective approaches in the field of translation. This study will serve as a valuable resource not only for translators, but also for linguists and cultural scholars.